2017
DOI: 10.1155/2017/1439486
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Hospital-Referred Head Injury in Ardabil City

Abstract: Background and Purpose. Trauma is the leading cause of death for youth in developing countries. Given the prevalence of head trauma (HT) in society and its complication and burden, the epidemiologic study of head trauma is necessary and is the main aim of this study. Materials and Methods. This retrospective population-based survey describes the epidemiology of head injury in a defined population in Ardabil city. It includes all 204 patients with head injury referred to the University Hospital of Ardabil, Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…While the men-to-women population ratio was not signi cantly different in Iran and the study area (13), men-to-women ratio of AAIRHI was 4:1 in the present study. HI ratio of men to women was uctuated between 2.5 and 5 in other studies in Iran (17,19), which consistent with the results of this study. An explanation for this is that females aren't motorcyclists in Iran and men often participate in high risk activities away from home and use derives more heavy and industrial vehicles and motorcycles compared to women and this may relate the low incidence of HI in women in Iran.…”
Section: Discussionsupporting
confidence: 93%
“…While the men-to-women population ratio was not signi cantly different in Iran and the study area (13), men-to-women ratio of AAIRHI was 4:1 in the present study. HI ratio of men to women was uctuated between 2.5 and 5 in other studies in Iran (17,19), which consistent with the results of this study. An explanation for this is that females aren't motorcyclists in Iran and men often participate in high risk activities away from home and use derives more heavy and industrial vehicles and motorcycles compared to women and this may relate the low incidence of HI in women in Iran.…”
Section: Discussionsupporting
confidence: 93%
“…There is a significant relation between seasons and traffic accidents as the main cause of trauma, such that this rate was higher in summer that can be related to widespread use of motorbike in the hot season and increased traffic agriculture and rural areas [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these had reported that fall is the most common cause of TBI. Study have often paid less attention or even ignored mild TBI and elder patients [ 10 , 11 ]. Additionally, older adults with TBI are at greater risk of morbidity and mortality compared to the younger patients [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%